2017
DOI: 10.1038/s41467-017-01560-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of developmental lineage relationships in the mouse mammary gland by single-cell RNA profiling

Abstract: The mammary epithelium comprises two primary cellular lineages, but the degree of heterogeneity within these compartments and their lineage relationships during development remain an open question. Here we report single-cell RNA profiling of mouse mammary epithelial cells spanning four developmental stages in the post-natal gland. Notably, the epithelium undergoes a large-scale shift in gene expression from a relatively homogeneous basal-like program in pre-puberty to distinct lineage-restricted programs in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
237
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(283 citation statements)
references
References 62 publications
(83 reference statements)
31
237
6
Order By: Relevance
“…4A). Concomitantly with the scRNAseq data, FACS analysis of the cancer epithelial cells revealed that Elf5 forced differentiation of the luminal progenitors, defined by a decrease in the proportion of Sca1 low /CD49b + progenitor cells 2 within the luminal (EpCam+/CD49f+) population (Fig 2D).We plotted each of our epithelial cells against the gene expression signatures for the epithelial cell lineages of the normal mammary gland23 to reveal the phenotypic similarity of our MMTV-PyMT epithelial cell clusters to those lineages currently recognised. Ternary plots shown inFig.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…4A). Concomitantly with the scRNAseq data, FACS analysis of the cancer epithelial cells revealed that Elf5 forced differentiation of the luminal progenitors, defined by a decrease in the proportion of Sca1 low /CD49b + progenitor cells 2 within the luminal (EpCam+/CD49f+) population (Fig 2D).We plotted each of our epithelial cells against the gene expression signatures for the epithelial cell lineages of the normal mammary gland23 to reveal the phenotypic similarity of our MMTV-PyMT epithelial cell clusters to those lineages currently recognised. Ternary plots shown inFig.…”
mentioning
confidence: 79%
“…0 3). We used the mammary gland hierarchy gene signature 23 To gain insights in this definition, we used GSVA 26…”
Section: Dynamic Relationship and States Of The Malignant Lineages Ofmentioning
confidence: 99%
“…Despite ongoing discussion in this area, a considerable body of work supports specific mammary populations as the candidate cells‐of‐origin for breast cancer subtypes. Finally, techniques such as scRNA‐seq and mass cytometry (CyTOF) are exposing heterogeneity within the basal and luminal compartments (Bach et al , ; Pal et al , ; Giraddi et al , ; Nguyen et al , ), indicating the necessity of further dissecting precursor–progeny relationships and developmental correlates of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Note that multiple apexes of a lineage can in principle exist (see Fig. 2), as is for instance conjectured for mouse mammary epithelium lineage (23).…”
Section: Principle 1 Adult Cell Lineage Hierarchies Of Renewing Tissmentioning
confidence: 77%